Blood oxidative stress and metallothionein expression in Rett syndrome: Probing for markers. (2nd April 2016) - Pintaudi, Maria; Veneselli, Edvige; Voci, Adriana; Vignoli, Aglaia; Castiglione, Dora; Calevo, Maria Grazia; Grasselli, Elena; Ragazzoni, Milena; Cogliati, Francesca; Calzari, Luciano; Scornavacca, Giulia Federica; Russo, Silvia; et al.
Abstract: Objectives : Oxidative stress seems to be involved in Rett syndrome (RTT). The aim of this study was to assess the antioxidant status in RTT children with MECP2 gene mutations with respect to healthy controls, and to explore novel blood antioxidant markers for RTT severity. Methods : In erythrocytes from RTT females aged 2–14 years ( n = 27) and age-matched controls ( n = 27), we measured the levels of malonaldehyde and the activity of two antioxidant enzymes, Cu/Zn-superoxide dismutase and catalase, by spectrophotometric assays. In leukocytes, the expression of metallothioneins, the main non-enzymatic antioxidants, was assessed by real-time RT-PCR. In nine selected RTT children, methylome analysis was also performed. Results : Blood of RTT patients showed increased lipid peroxidation and a dysregulated pattern of MT expression, while enzymatic activities did not change significantly with respect to controls. Moreover, we observed no epigenetic dysregulation in CpG-enriched promoter regions of the analysed genes but significant hypomethylation in the random loci. Conclusions : As the haematic level of MT-1A directly correlates with the phenotype severity, this metallothionein can represent a marker for RTT severity. Moreover, the attempt to link the level of blood oxidative stress with MECP2 mutation and specific clinical features led us to draw some interesting conclusions.